Modelling the adoption of mobile payment system for primary and secondary school student examination fees in developing countries: Tanzanian experience - Tossy, Titus (International Journal of Information Technology and Business Management, 2024)
Article published by the International Journal of Information Technology and Business Management 29th July 2014. Vol.27 No.1